First chromosome analysis of Thai pufferfish Pao cochinchinensis (Steindachner, 1866) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Pissaparn M, Phimphan S, Chaiyasan P, Tanoamtong A, Liehr T, Suwannapoom C, Reungsing M, Supiwong W. 2020. First chromosome analysis of Thai pufferfish Pao cochinchinensis (Steindachner, 1866). Biodiversitas 21: 4309-4316. Here first analysis of chromosomes and nucleolar organizer region (NOR) pattern in pufferfish Pao cochinchinensis (Steindachner, 1866) was undertaken. Chromosomal preparations were obtained from kidney of P. cochinchinensis from Chi River basin in Thailand. Chromosomal characteristics were analyzed by Giemsa staining, Ag-NOR banding as well as fluorescence in situ hybridization (FISH) using microsatellites d(CA)15 and d(CGG)10 probes. P. cochinchinensis had 2n = 40 with the fundamental number (NF) 74, both in male and female. The karyotype exhibited 12 metacentric (m), 10 submetacentric (sm), 12 acrocentric (a) and 6 telocentric (t) chromosomes. No differentiated heteromorphic sex chromosomes were observed. NORs were located on short arms adjacent to telomere of the metacentric chromosome pair 4, which coincide with signals of d(CGG)10 probe. FISH with d(CGG)10 sequences were also displayed at the telomeres of most other chromosomes, whereas d(CA)15 repeats highly accumulated throughout almost all entire chromosomes except for centromeric regions. The results of conventional Giemsa staining presented the differentiation even the same genus. The localization of NORs on one pair of chromosomes only is a common characteristic found in many fish groups as well as other vertebrates. Mapping of two distinct microsatellites demonstrated the remarkable chromosomal diversification that characterizes evolution in the genus Pao. Both, conventional and molecular cytogenetics are excellent tools to study, and better understand chromosomal evolution, as well as to uncover biodiversity among fishes.
Keywords: Chromosome, FISH, karyotype, Nucleolar Organizer Region, Pao cochinchinensis